홍채 변형 환자에서 데스메막박리내피각막이식술 후 아트로핀을 이용한 이식편의 재유착 유도 - 양승안; 강민승; 신종훈; 이지은 (Daihan angwa haghoi jabji, 2023)
목적: 홍채 변형이 있는 환자에게 데스메막박리자동내피각막이식(Descemet stripping automated endothelial keratoplasty, DSAEK) 시행 후 아트로핀을 이용하여 이식편의 재유착을 유도한 증례를 보고하고자 한다. 증례요약: 76세 남자가 우안 수포성 각막병증 소견으로 각막이식을 위해 의뢰되었다. 우안 유리체절제술, 공막고정술의 수술력이 있었고 이로 인한 홍채 변형이 있었다. DSAEK 시행 후 전방에 주입한 공기 방울의 후방 이동과 이식편의 분리 소견이 관찰되었다. 아트로핀 점안 및 공기재주입술 시행 후 이식편이 수여각막에 잘 유착됨을 확인하였다. 술 후 3개월 경과 관찰 결과 이식편은 잘 유착된상태를 유지하였으며 각막 투명도 또한 잘 유지되었다. 결론: 유리체절제술을 시행하고 홍채 변형이 있는 안에서 DSAEK을 시행하였을 때 공기 방울의 후방 이동이 관찰된다면 아트로핀을이용하여 공기의 이동을 막고 이식편의 재유착을 유도할 수 있을 것으로 생각된다. Purpose: To report successful graft reattachment using atropine after Descemet’s membrane stripping automated endothelial keratoplasty (DSAEK) in iris deformity. Case summary: A 76-year-old male was referred for decreased visual acuity due to bullous keratopathy in his right eye. He had previously undergone several eye surgeries, including vitrectomy and intraocular lens fixation, because of retinal detachment, which caused the iris deformity. DSAEK was performed, but the graft detached because of an air bubble in the posterior chamber. Atropine was used to move the air into the anterior chamber. The graft was attached the next day, and maintained during 3 months of follow-up. Conclusions: Atropine is an effective treatment option for cases with air bubble migration to the posterior chamber, leading to graft detachment after DSAEK in iris deformity. KCI Citation Count: 0